Extremely low-frequency electromagnetic field (ELF-EMF) induced alterations in gene expression and cytokine secretion in clear cell renal carcinoma cells - Aleksandra Cios; Martyna Ciepielak; Krystyna Lieto; Damian Matak; Sławomir Lewicki; Małgorzata Palusińska; Wanda Stankiewicz; Łukasz Szymański (Nofer Institute of Occupational Medicine, 2024)
Background The study aimed to investigate the influence of extremely low-frequency electromagnetic fields (ELF-EMF) on clear cell renal cell carcinoma (ccRCC) by assessing alterations in gene expression and the secretion of cytokines and chemokines. Material and Methods Three ccRCC cell lines (786-O, 769-P, and CAKI-1) and a healthy HEK293 cell line were subjected to ELF-EMF exposure (frequency 50 Hz, magnetic field strength 4.5 mT) for 30 min daily for 5 days. The study examined the expression of ADAM28 , NCAM1 , and VEGFC genes, along with the secretion of 30 cytokines and chemokines. Results Notably, primary tumor-derived cell lines, but not those from metastatic sites, exhibited ADAM28 gene expression, which increased following ELF-EMF exposure. A statistically significant reduction in VEGFC gene expression was observed in 769-P cells after ELF-EMF exposure. Additionally, NCAM1 gene expression was upregulated in HEK293, 769-P, and 786-O cells, representing normal embryonic kidney cells and primary tumor cells, but not in CAKI-1 cells, which model metastatic sites. After EMF exposure, there was a statistically significant decrease in transforming growth factor β1 (TGF-β1) concentration in the cell culture supernatants of HEK293 and CAKI-1 cell lines, with no other significant changes in the secretion of tested cytokines. Conclusions Given the study's findings and available research, caution is warranted when drawing conclusions about the potential inhibitory effect of ELF-EMF on ccRCC progression. Standardization of experimental models is imperative when assessing the effects of EMF in a human context. Med Pr Work Health Saf. 2024;75(2):133-141